Government employees ; Louie Ocampo ; Buko [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Features the unhealthy work culture in government offices, the effect on the plan of reorganization; interviews with Louie Ocampo, a music composer; and the Congress exposing the "buko" controversy.
Government employees (15 min.) -- Louie Ocampo (13 min.) -- Buko (20 min.)
VHS.
Keywords: Ocampo, Louie; Philippine Coconut Industry; Coconut industry -- Philippines; Musicians -- Philippines; Retirement -- Philippines; Philippines -- Officials and employees; Philippines -- Officials and employees -- Salaries, allowances, etc